2016
DOI: 10.1073/pnas.1613279113
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery from the effects of early monocular deprivation is enabled by temporary inactivation of the retinas

Abstract: A half-century of research on the consequences of monocular deprivation (MD) in animals has revealed a great deal about the pathophysiology of amblyopia. MD initiates synaptic changes in the visual cortex that reduce acuity and binocular vision by causing neurons to lose responsiveness to the deprived eye. However, much less is known about how deprivation-induced synaptic modifications can be reversed to restore normal visual function. One theoretically motivated hypothesis is that a period of inactivity can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 71 publications
2
58
0
Order By: Relevance
“…Subsequent TTX injections were made every 48 hr using the original injection site so as to avoid having to make an additional puncture. A single dose of intravitreal TTX has been shown to effectively eliminate visual responses for at least 48 hr (Stryker & Harris, ; Linden, Heynen, Haslinger, & Bear, ; Fong et al, ). All animals that received binocular or monocular TTX injections had their deprived eye opened prior to the first intravitreal injection, and the same injection procedure was followed for both groups.…”
Section: Methodssupporting
confidence: 83%
See 3 more Smart Citations
“…Subsequent TTX injections were made every 48 hr using the original injection site so as to avoid having to make an additional puncture. A single dose of intravitreal TTX has been shown to effectively eliminate visual responses for at least 48 hr (Stryker & Harris, ; Linden, Heynen, Haslinger, & Bear, ; Fong et al, ). All animals that received binocular or monocular TTX injections had their deprived eye opened prior to the first intravitreal injection, and the same injection procedure was followed for both groups.…”
Section: Methodssupporting
confidence: 83%
“…Binocular retinal inactivation with intravitreal TTX injection has recently been shown to promote both anatomical and behavioral recovery from 1 week of MD in kittens (Fong et al, ) so we examined the ability for this treatment to promote recovery from 6 weeks of MD. TTX is a voltage‐gated sodium channel blocker that when injected into the posterior chamber of the eye temporarily abolishes retinal ganglion activity for at least 48 hr (Stryker & Harris, ; Linden et al, ; Fong et al, ). Binocular inactivation of retinal ganglion cells for 10 days following 6 weeks of MD stimulated about 50% recovery, leaving deprived neurons still significantly smaller than non‐deprived neurons by an average of 17% ( U = 0, p = .028; Figure c1–3).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Thus, access to completely dark environments for a sufficient duration of time with proper support to guarantee safety and well-being may pose challenges for widespread use. Interestingly, visual deprivation for several days by binocular intravitreal injections of the pufferfish toxin tetrodotoxin promotes similar fast visual recovery in amblyopic cats (Fong et al, 2016), raising the possibility of developing novel pharmacological techniques to transiently block vision, if adequate safety measures can reliably be ensured. Blindfolding may offer another solution—one study suggested that blindfolding normally sighted adults for 5 days leads to rapid changes in experience-dependent functional neural connectivity (Merabet et al, 2008).…”
Section: Environmental and Behavioral Treatmentsmentioning
confidence: 99%